2021
DOI: 10.1002/anie.202105425
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive Regulation of Cellular Morphology Using a Photoswitchable Mechanical DNA Polymer

Abstract: The extracellular matrix (ECM) in which the cells reside provides a dynamic and reversible environment. Spatiotemporal cues are essential when cells are undergoing morphogenesis, repair and differentiation. Emulation of such an intricate system with reversible presentation of nanoscale cues can help us better understand cellular processes and can allow the precise manipulation of cell function in vitro. Herein, we formulated a photoswitchable DNA mechanical nanostructure containing azobenzene moieties and dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Very recently, Sethi et al reported a photo-switchable DNA nanospring using azobenzene-incorporated DNA strands. 88 After light irradiation, due to the cis – trans conformational change of azobenzene, the DNA hairpin structures can be reversibly folded/unfolded to induce the shrinking/relaxation of the DNA nanospring.…”
Section: Dna-based Mechanical Regulatorsmentioning
confidence: 99%
“…Very recently, Sethi et al reported a photo-switchable DNA nanospring using azobenzene-incorporated DNA strands. 88 After light irradiation, due to the cis – trans conformational change of azobenzene, the DNA hairpin structures can be reversibly folded/unfolded to induce the shrinking/relaxation of the DNA nanospring.…”
Section: Dna-based Mechanical Regulatorsmentioning
confidence: 99%
“…Furthermore, our group recently developed a light-controlled dynamic DNA polymer which can extend and shrink reversibly by photoirradiation. [26] This photofunctionalized DNA polymer could behave as an ECM and reversibly changed the presentation of nanocues to the cells to control the morphology of mesenchymal stem cells. Significant changes in morphology, F-actin organization and vinculin distribution were observed among the cells.…”
Section: Dynamic Dna Ecm Like Matrixmentioning
confidence: 99%
“…A tool for mimicking ECM [26] in 3D cell culture (Figure 2a). [29] Thermo-reversible DNA hydrogels with high stretchability and integrated molecular toolbox of DNA tension probes were prepared and used as a fluorescent mechanochromic matrix (Figure 2b).…”
Section: Adhered To Glass Coated Aptesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Sethi et al formulated a photoswitchable DNA nanostructure to dynamically regulate the spatial distance of RGD with photoirradiation, which can induce a significant morphology change in cells. 20 Yet, the previous methods are generally based on transitions between double-stranded DNA (dsDNA) and the DNA hairpin, whose mechanical strength is not stable enough for precise control of the spatial distribution between different ligands. On the other hand, DNA origami-based nanocalipers can present ligands at well-defined positions but lack stimuliresponsive reconfigurable properties.…”
Section: ■ Introductionmentioning
confidence: 99%